Analysis of the partnering relations of Polish, Slovak and Ukrainian construction enterprises - Radziszewska-Zielina, Elżbieta (Technological and Economic Development of Economy, 2010)
The present author has conducted research on partnering co‐operation in construction industry. The research was carried out using the questionnaire method in selected administrative regions of the following three countries: Poland, Slovakia and Ukraine. It was assumed that analysis would mainly concern medium and large construction enterprises and that the respondents would include selected experts in these enterprises: owners, enterprise managers, construction site managers. The final assessment of the partnering relations of Polish and Slovak construction enterprises is similar. Partnering co‐operation in construction industry is already noticeable but still remains on a low level. The assessment of the partnering relations in Ukrainian construction enterprises is lower than in the Polish and Slovak ones.Article in English.Lenkijos, Slovakijos ir Ukrainos statybos įmonių partnerystės santykių analizėSantrauka. Autorė atliko partnerių bendradarbiavimo statybos pramonėje tyrimą. Tyrimas atliktas anketinės apklausos metodu, respondentai apklausti pasirinktuose Lenkijos, Slovakijos ir Ukrainos administraciniuose regionuose. Analizė apėmė vidutines ir dideles statybos įmones. Buvo apklausti įmoniu savininkai, vadovai, statybų vadovai. Tyrimas atskleide, kad partnerių bendradarbiavimas statybos pramoneje jau yra pastebimas, tačiau vis dar reikiamai neišpletotas. Įvertinimas rodo, jog partnerystes santykiu lygis Lenkijos ir Slovakijos statybos įmonėse yra panašus. Partnerystes santykiu lygis tarp Ukrainos statybos įmonių yra menkesnis nei tarp Lenkijos ar Slovakijos įmonių.Reikšminiai žodžiai: partnerystė, partnerystės santykių lygis, anketinės apklausos metodas, statybos įmonės.First published online: 10 Feb 2011